Driving change: the 2011 National Beef Quality Audit - Igo, Jessica Leigh, author; Belk, Keith, advisor; Tatum, Daryl, committee member; Woerner, Dale, committee member; Chapman, Phillip, committee member (Colorado State University. Libraries, 2012)
The National Beef Quality Audit - 2011 evaluated the current status and progress being made towards quality and consistency of cattle, carcasses, and beef products produced by the U.S. fed beef population since the introduction of the National Beef Quality Audit in 1991. The objectives of this research were to determine how each beef market sector defines seven identified quality categories, estimates willingness to pay (WTP) for specified quality categories within each beef market sector, and establishes a best-worst (BW) scaling for the identified quality attributes. Face-to-face interviews were conducted using a modern, dynamic routing instrument over an 11-mo period (February to December 2011) with representatives of the following beef market sectors: Government and Allied Industries (n = 47); Feeders (n = 59); Packers (n = 26); Food Service, Distribution, and Further Processors (n = 48); and Retailers (n = 30). To accomplish the objectives, all responses were characterized using seven pre-established quality categories as the basis for asking interviewees the WTP and BW scaling questions. To determine WTP of the beef market sectors for U.S. fed beef, it was first important to understand what "quality" meant to each sector as it related to the U.S. fed beef products they purchase. To achieve this, "quality" was divided into seven pre-established categories: (1) How and where the cattle were raised, (2) Lean, fat, and bone, (3) Weight and size, (4) Cattle genetics, (5) Visual characteristics, (6) Food safety, and (7) Eating satisfaction, and interviewees in each beef market sector were asked to explain iii exactly which quality-related details/practices were important within each category. Overall, "Food safety" was the attribute of greatest importance to all beef market sectors except Feeders, who ranked "How and where the cattle were raised" as the most important. "Eating satisfaction" was the attribute of second most importance to all beef market sectors, except Feeders. Feeders ranked "Weight and size" as the second most important. Overall, "How and where the cattle were raised" had the greatest odds (0.25) of being considered a "non-negotiable requirement" before the raw material for each sector would be considered at all for purchase, and differed (P < 0.05) from "Visual characteristics" (0.14), "Lean, fat, and bone" (0.12), "Eating satisfaction" (0.12), "Cattle genetics" (0.10), and "Weight and size" (0.06). Of all market sectors combined, "Eating satisfaction" calculated the highest average percentage premium (11.1%), but only differed (P < 0.05) from "Weight and size" (8.8%). Most notably, when a sector said that "Food safety" was a "non-negotiable requirement," no sector was willing to purchase the product at a discounted price if the "Food safety" of the product could not be assured.
Keywords: market survey; best-worst scaling; willingness to pay; beef; beef quality